VARIASI PROPORSI SEL DAN DIMENSI SERAT KAYU GMELINA (Gmelina arborea Roxb.) JENIS PERMUDAAN BIJI DAN TRUBUSAN PADA ARAH RADIAL DARI BOJONEGORO - , INDAH SULISTIOWATI, Harry Praptoyo, S.Hut., MP. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The silviculture system of Gmelina arborea Roxb. can be done by generative or vegetative regeneration. One method of vegetative regeneration is a coppice method but not much data collection about wood anatomy research from different tree regeneration. In order for optimal uses of wood, so we need to know about cells proportion and fiber dimensions of wood from coppice method. This study used Completely Randomized Design with two factors namely regeneration method (seed and coppice method) and radial position by each centimeter from pith to bark (R1, R2, R3, R4, R5, R6, R7, R8, and R9) with two replications. Parameters which tested involve proportion of cells (vessel, parenchyma, rays, fiber) and fiber dimensions (fiber length, fiber diameter, lumen diameter, and fiber wall thickness). All parameters will be evaluated using SPSS Statistical Program. Preparation of test samples followed the LPHH guidance. The result of this study showed that proportion of vessel, parenchyma, rays, and fiber from seed regeneration in consecutively is 7,54%, 11,47%, 24,60%, and 56,39%. Fiber length, fiber diameter, lumen diameter, and fiber wall thickness from seed regeneration is 0,968 mm, 22,22 Î¼m, 19,91 Î¼m, and 1,156 Î¼m. The average proportion of vessel, parenchyma, rays, and fiber from coppice method is 8,652%, 10,48%, 19,84%, and 61,03%. The value of fiber length, fiber diameter, lumen diameter, and fiber wall thickness in consecutively is 1,080 mm, 21,38 Î¼m, 19,13 Î¼m, and 1,124 Î¼m. The regeneration method factor was significant affected on rays proportion, fiber proportion, and fiber length. Radial variation by each centimeter factor was not significant affected on wood cells proportion and fiber dimensions